'Is gestational diabetes a severe illness?' exploring beliefs and self‐care behaviour among women with gestational diabetes living in a rural area of the south east of China. (18th April 2016) - Ge, Li; Wikby, Kerstin; Rask, Mikael
Abstract: Objective: This study explores beliefs about illness and health and self‐care behaviour among women with gestational diabetes living in a rural area of the south east of China. Design: A qualitative exploratory study using semi‐structured interviews and qualitative content analysis. Setting: A hospital located in the outskirts of a city in the south east of China. Participants: Seventeen women with gestational diabetes in 34–38th pregnant weeks. Results: The beliefs about gestational diabetes among the women in the present study were found to be bidirectional. Some of them feared the illness and its negative influence on health, while others believed that it was not a severe illness and disbelieved the diagnosis of gestational diabetes. They related their illness and health to the individual, social and natural factors. They mainly sought help from the professional sector, but did not fully comply with the professionals' advice. Diet control and exercise were their main self‐care measures, but none of them self‐monitored their blood glucose. They demonstrated their misunderstanding about diet control and self‐monitoring of blood glucose. Conclusions: This study highlighted the serious lack of knowledge, lower level of risk awareness and poor self‐care behaviour among women in this group. Health professionals were found to be the most important source of knowledge about gestational diabetes for these women. The influence of Chinese culture was demonstrated. Gestational diabetes among these women can most likely be improved by training the health professionals and by health education involving individuals, families and the rural communities.